The Analysis of Factors Influencing Customer in Choosing Financial Service Product at Sharia Multifinance - Deni Nasri; Mukhamad Najib; Eng Saiful Anwar (ILTIZAM Journal of Shariah Economics Research, 2020)
In recent years consumer behaviour plays an important role on influencing customers' preferences to use a financing service. Contemporary consumers are becoming more selective in their choices, as they are more well-informed of a particular product or service. This research investigates the decision-making process which influence customers in choosing a financing service, by analysing the influence of religiosity, TPB (attitude towards behavior, subjective norm, perceived behavioral control), and product attribute that drives customers' intent in choosing financial services in sharia multifinance. To address this notion, we collected sample feedback from 160 respondents, who are active customers of Unit Usaha Syariah (UUS) multifinance ABC. The methododology used in this research is Structural Equation Modeling-Partial Least Square (SEM-PLS). The result shows that factors such as religiosity, attitude towards behavior, subjective norms and product attribute affect consumers' intention in purchasing a financing service. On the other hand, perceived behavioral control has no significant influence on consumers' decision-making. Therefore, it is imperative for those involved in the sharia multifinance industry to gain more insight in order to perceive market opportunities based on consumer behavior by developing suitable marketing strategies in order to capture their interest to opt for financing services in sharia multifinance. Keywords: Consumer behaviour, religiosity, TPB, attribute product, sharia multifinance